Excision margin of T3 basal cell carcinoma in maxillofacial area: A retrospective cohort study of Asians. (18th December 2020) - Sheng, Surui; Qi, Shuqun; Pan, Jian; Qin, Xingjun
Abstract: Objectives: Basal cell carcinoma is the most common skin cancer worldwide. Surgical excision is considered as the mainstay of treatment, while the evidence of excision margin in advanced stage is lacking, especially in maxillofacial area. Materials and Methods: We conducted a 2‐center retrospective cohort study. Disease‐free survival rate was estimated for 116 Asian patients with T3 basal cell carcinoma in maxillofacial area who received stand surgical excision with margin of 3–5 mm (Group A), 6–9 mm (Group B), and 10–15 mm (Group C). Results: For the entire cohort, five‐year disease‐free survival rates of Groups A, B, and C were 82.1%, 93.5%, and 92.4%, respectively. When compared with Group B, Group A was correlated with lower disease‐free survival rate (HR 5.48, p  = .04), and Group C was not associated with different disease‐free survival rate (HR 0.85, p  = .62). Perineural invasion ( p  = .006) and pathologic subtypes of infiltrative basal cell carcinoma ( p  = .01) were independent prognosticator for disease‐free survival rate. Conclusions: This multicenter cohort study validated that T3 basal cell carcinoma Asian patients of maxillofacial area treated with excision margin of 6–9 mm had a substantial benefit of disease‐free survival rate and skin conservation.